2001
DOI: 10.1001/archinte.161.21.2581
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of an Intranasal Corticosteroid Compared With an Oral Antihistamine in the As-Needed Treatment of Seasonal Allergic Rhinitis

Abstract: As-needed intranasal corticosteroids reduce allergic inflammation and are more effective than as-needed H(1) receptor antagonists in the treatment of seasonal allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 16 publications
1
57
0
6
Order By: Relevance
“…Studies of INS therapy conducted in 2009 demonstrated efficacy in alleviating ocular symptoms, supporting earlier findings on the utility of this drug class as an ocular allergy therapy, including comparative research that indicates that INS provide equal or greater relief of ocular allergy symptoms as compared with intranasal [50] or oral antihistamines [40,[51][52][53]. Data published in the past year are reviewed below.…”
Section: Intranasal Corticosteroidssupporting
confidence: 54%
“…Studies of INS therapy conducted in 2009 demonstrated efficacy in alleviating ocular symptoms, supporting earlier findings on the utility of this drug class as an ocular allergy therapy, including comparative research that indicates that INS provide equal or greater relief of ocular allergy symptoms as compared with intranasal [50] or oral antihistamines [40,[51][52][53]. Data published in the past year are reviewed below.…”
Section: Intranasal Corticosteroidssupporting
confidence: 54%
“…When the medications prescribed for SR patients in other clinics before admission to our clinic and those suggested by our clinic are compared, statistically significant differences and important therapeutic defects were noted. For example, the rate of nasal steroid usage, which is the drug of choice for SR [30], was only 13.1% before admission. In addition, these patients were mostly prescribed antihistamines as a monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The RQLQ has been used in several trials to assess the effect of intranasal glucocorticosteroids (1085,(1089)(1090)(1091)(1092)(1093)(1094), oral H 1 -antihistamines in seasonal (1095)(1096)(1097), perennial (1077,1078) and PER (1066,1067,1098), the combination of intranasal glucocorticosteroids and oral H 1 -antihistamines (1099), leukotriene receptor antagonists (1100, 1101), allergen immunotherapy in pollinosis (1102)(1103)(1104), omalizumab, an anti-IgE monoclonal antibody (768,1105), allergen avoidance (1106) and homeopathy (1107). Studies have also been performed in children (1108).…”
Section: Evolution Of Qol During Interventionsmentioning
confidence: 99%